Comparative study of the severity of neurological damage in two cohorts of patients with traumatic cervical spinal cord injury. - Muñoz-Maldonado, Maria Carolina (2023)
Objetive: Compare the severity of neurological damage and the clinical and demographic characteristics of two cohorts of patients with traumatic cervical spinal cord injury (CTSCI) at discharge from rehabilitation, in two specialized institutions. Material and Methods: This is an analytical and retrospective observational study, comparing patients with CTSCI treated at the National Institute of Rehabilitation (INR) of Peru and the Institut Guttmann of Spain. Clinical, demographic, and clinical outcome variables were described and analyzed. Results: The CTSCI in both groups affects males in more than 85%, the mean age of the Guttmann I. patients was 46.35 ± 21.03 years, and the INR was 37.1 ± 1.47 years. The time elapsed to the surgical intervention was 3.61 and 10.39 days; and the time from the injury to the first attention in the rehabilitation institutions was 70.32 and 306.7 days in the Guttmann Institute and the National Rehabilitation Institute, respectively. 70.8% of INR patients had greater severity in the ASIA Deficiency Scale (Grade “A” and “B”) compared to 41.9% of I. Guttmann. Conclusions: INR’s patients have greater severity of neurological damage and start specialized care in comprehensive rehabilitation late.